Genetically determined blood pressure, antihypertensive drug classes, and risk of stroke subtypes. - Georgakis, MK; Gill, D; Webb, AJS; Evangelou, E; Elliott, P; Sudlow, CLM; Dehghan, A; Malik, R; Tzoulaki, I; Dichgans, M (American Academy of Neurology, 2020)
Objective: We employed Mendelian randomization to explore whether the effects of blood pressure (BP) and BP-lowering through different antihypertensive drug classes on stroke risk vary by stroke etiology.